PROTOTIPE INTEGRATIVE WRITING MODEL (IWM) BERBASIS PSYCHOWRITING-MYERS-BRIGGS TYPE INDICATORS (MBTI) DALAM PEMBELAJARAN MENULIS - Ahmadi, Anas (Inovasi: Jurnal Diklat Keagamaan, 2017)
Motivation factors play an important role in influencing learning.Motivation plays a very important role in human efforts to achievethe desired goals, in the field of education and other purposes.Motivation is impetus, it means there is a conscious effort toinfluence one’s behavior to move his heart to act to do something toachieve certain results or goals Purwanto (1996: 71). With themotivation learners can develop activities and initiatives that isable to direct and maintain persistence in learning activities. Thereare several forms and ways to foster motivation in school activitiessuch as gift giving, score, praise, punishment, competition,repetition, and interest.